2015
DOI: 10.1007/s12040-015-0624-3
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based assessment of landslide susceptibility using certainty factor and index of entropy models for the Qianyang County of Baoji city, China

Abstract: The main goal of this study is to produce landslide susceptibility maps for the Qianyang County of Baoji city, China, using both certainty factor (CF) and index of entropy (IOE) models. At first, a landslide inventory map was prepared using earlier reports and aerial photographs as well as by carrying out field surveys. A total of 81 landslide locations were detected. Out of these, 56 (70%) landslides were randomly selected as training data for building landslide susceptibility models and the remaining 25 (30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(52 citation statements)
references
References 79 publications
(65 reference statements)
3
49
0
Order By: Relevance
“…Numerous methods have been produced to assess landslide susceptibility at a regional scale, including direct geomorphological mapping (analysis of landslide inventories), heuristic approaches, statistical methods, physically-based models [7][8][9], and newly-developed machine learning models [10,11]. More detailed information of different models for landslide susceptibility mapping can be found in the literature [8,[12][13][14][15][16][17][18][19][20][21][22][23]. However, all the methods have both advantages and drawbacks, and no one method is accepted universally for the effective assessment of landslide hazards due to the complex nature of landslides [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous methods have been produced to assess landslide susceptibility at a regional scale, including direct geomorphological mapping (analysis of landslide inventories), heuristic approaches, statistical methods, physically-based models [7][8][9], and newly-developed machine learning models [10,11]. More detailed information of different models for landslide susceptibility mapping can be found in the literature [8,[12][13][14][15][16][17][18][19][20][21][22][23]. However, all the methods have both advantages and drawbacks, and no one method is accepted universally for the effective assessment of landslide hazards due to the complex nature of landslides [11].…”
Section: Introductionmentioning
confidence: 99%
“…Yao [9] trained one-class and two-class support vector machine (SVM) methods to map landslide susceptibility, comparing their accuracies with logistic regression, and concluded that two-class SVM possesses the best prediction result. Kavzoglu et al [18][19][20][21][22][23] evaluated landslide susceptibility mapping using GIS-based multi-criteria decision analysis, support vector machines, and many other methods, and showed that SVM outperformed the conventional logistic regression method in the mapping of landslides. The above studies show the results in different regions with their own geo-environmental factors, and selecting a proper model should be performed for landslide susceptibility mapping through comparisons of landslide models.…”
Section: Introductionmentioning
confidence: 99%
“…The proximity of streams has been considered for the preparation of landslide susceptibility maps by many researchers (Akgun et al, 2008;Basharat et al, 2016;Kanwal et al, 2016;Wang et al, 2015). In our study area, many small tributaries feed main rivers (Indus and Hunza).…”
Section: Hydrologymentioning
confidence: 99%
“…The proximity of streams has been considered for the preparation of landslide susceptibility maps by many researchers (Akgun et al, 2008;Basharat et al, 2016;Kanwal et al, 2016;Wang et al, 2015). In our study area, many small tributaries feed main rivers, Indus and Hunza.…”
Section: Hydrology 10mentioning
confidence: 99%